Socio-Demographic, Clinical and Psychological Profile of Frailty Patients Living in the Home Environment and Nursing Homes: A Cross-Sectional Study - Muszalik, Marta; Kotarba, Agnieszka; Borowiak, Ewa; Puto, Grażyna; Cybulski, Mateusz; Kȩdziora-Kornatowska, Kornelia (Frontiers in Psychiatry, 2021)
Introduction: Frailty syndrome, as a physiological syndrome, is characterized by a gradual decline in physiological reserve and a lowered resistance to stress-inducing factors, leading to an increased risk of adverse outcomes. It is significantly connected with dependence on care and frequent hospitalizations. Objectives: The aim of the study was to describe socio-demographic, clinical and psychological profile of frailty older adults living in their own homes and to nursing homes. Methods: The study was conducted with 180 patients who were over 60 years of age, the mean(±SD) was 74.1(±8.8) years. Among the subjects, 90 individuals were community-dwelling older adults. The survey used a list of socio-demographic questions, as well as the following scales: Mini-Mental State Examination (MMSE), Geriatric Depression Scale (GDS), SHARE-FI, and The World Health Organization Quality of Life (WHOQOL-Bref). Results: Pre-frailty was confirmed in 49 (27.2%) patients, and frailty syndrome was noticed in 47 patients (26.1%). The prevalence of frailty syndrome in the study group was related to: place of living (p<0.001), age (p<0.001), widowhood (p<0.001), a poor economic situation (p<0.001), basic education level (p<0.001), living alone (p<0.001), longer duration of illness (p<0.001), comorbidities (p<0.001), more medications taken (p<0.001), deterioration of hearing (p=0.003), impairment of cognitive functions (p<0.001), depression (p<0.001), and decreased quality of life (p<0.001). Discussion: A lot of socio-demographic and medical factors, particularly cognitive and mental functioning were connected with the prevalence and progression of frailty syndrome in the study group. Quality of life was significantly dependent on the presence of frailty syndrome, both in homes and in nursing homes.